Searching for material symmetries in the burr wood of thuja by a direct contact ultrasonic method on spherical samples - El Mouridi, Mohammed; Laurent, Thierry; Brancheriau, Loïc; Arnould, Olivier; Famiri, Abderrahim; Hakam, Abdelillah; Gril, Joseph (Maderas. Ciencia y Tecnología, 2025)
This work is part of a program that aims at studying the burr wood of thuja (Tetraclinis articulata). The goal of this work is to identify material symmetries of burr wood to improve its machining. To have a sufficient number of data and to limit the variability between samples, an ultrasonic experimental device, in direct contact on spherical samples, has been developed and improved. Until now, the geometry used in direct contact ultrasonic methods was either cubic or polyhedral allowing to obtain, on the same sample, 3 (cube) to 13 (polyhedron) measurements or usable data. By choosing a reasonable angular gap, the spherical geometry allows the ultrasonic velocity to be measured in 133 different directions on the same specimen. We present here the adaptation and development of the ultrasonic experimental device and results obtained on (i) aluminum chosen as a reference material, (ii) beech wood and (iii) burr wood of thuja.